Carbonate Templated Self-Assembly of an Alkylthiolate Bridged Cadmium Macrocycle - Lai, Wei (2013)
In the presence of Cd (ClO(4))(2) and base, a new mixed N,S-donor alkylthiolate ligand supported both carbonate formation from atmospheric CO(2) and self-assembly of a novel bis-capped puckered (CdS)(6) molecular wheel with 3-fold symmetry. The remarkable stability of the complex was demonstrated by slow intermolecular ligand exchange on the (2)J(HH) and J((111/113)Cd(1)H) time scales at elevated temperature. Both CO(2) and base were required to convert amorphous “CdLClO(4)” precipitated in the absence of air to the carbonate complex. The complex shares structural features with the ζ-carbonic anhydrase class associating Cd(II) with the biogeochemical cycling of carbon and is the first structurally characterized carbonate complex of any metal involving an alkylthiolate ligand.